1994
DOI: 10.1002/ajim.4700250310
|View full text |Cite
|
Sign up to set email alerts
|

Cancer mortality in workers employed at a transformer manufacturing plant

Abstract: This study examined mortality to December 31, 1989 in a cohort of 2,222 males employed between 1947 and 1975 at a transformer manufacturing plant in Canada, where there had been extensive use of transformer fluid, some containing polychlorinated biphenyls (PCBs). A combined cohort list of 2,222 names was independently obtained from plant management and union officials. Mortality of 1,939 workers with known birthdates was ascertained by record linkage with the Canadian Mortality Data-base. Standardized mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 29 publications
0
37
0
Order By: Relevance
“…An increased risk for NHL has also been suggested for high consumers of fish from the Baltic Sea, which is contaminated by PCBs and other organochlorines (44). One study of male capacitor-manufacturing workers with PCB exposure found an increased risk for NHL (45); another study found no increased risk (46).…”
Section: Resultsmentioning
confidence: 99%
“…An increased risk for NHL has also been suggested for high consumers of fish from the Baltic Sea, which is contaminated by PCBs and other organochlorines (44). One study of male capacitor-manufacturing workers with PCB exposure found an increased risk for NHL (45); another study found no increased risk (46).…”
Section: Resultsmentioning
confidence: 99%
“…Transformers were filled with PCBs, but the impregnation fluid was usually diluted with other chlorinated solvents (e.g. trichlorobenzene; , and sold under different names such as Askarel (Inerteen), Pyranol, Chlophen, Apirolio, and Derol (Kerns, 1975;Lees et al, 1987;Emmett et al, 1988;Kalina et al, 1991;Yassi et al, 1994;Altenkirch et al, 1996;Loomis et al, 1997;.…”
Section: Transformer Manufacture and Repairmentioning
confidence: 99%
“…Duration of employment was used to assess exposure in most of these studies Bertazzi et al, 1982Bertazzi et al, , 1987Nicholson & Selikoff, 1987;De Guire et al, 1988;Taylor et al, 1988;Liss, 1989;Petruska & Engelhard, 1991;Tynes et al, 1994;Yassi et al, 1994Yassi et al, , 2003Savitz & Loomis, 1995;Tironi et al, 1996;Kimbrough et al, 1999Kimbrough et al, , 2003Loomis et al, 1997;Mallin et al, 2004;Prince et al, 2006a, b;Ruder et al, 2006;Ahrens et al, 2007;Hopf et al, 2009bHopf et al, , 2010Hopf et al, , 2014Pesatori et al, 2013). In the remaining studies, exposure to PCBs was assessed using a variety of approaches, including job-exposure matrices (JEM), development of worker's exposure zones, and measurement of serum PCB concentrations.…”
Section: Studies Of Occupational Exposurementioning
confidence: 99%
See 2 more Smart Citations